The Dynamics of Identity Politics In Indonesia: A Study of Nurcholish Madjid's - Fitri, Donna Ramadhan; Miswardi, Miswardi; Yufriadi, Ferdi; Refliandi, Irvan; B, Syafriadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Islamic political power is not always related to Islamic parties. Nurcholish Madjid tried to convey a more substantial view of Islam, not just symbolism. This research uses the library research method. Research carried out using literature, both in the form of primary sources, namely research data sources obtained from original sources that contain this information and secondary sources, namely data sources obtained from books and other literature that discuss the topic of the problem. The data processing techniques in this study using content analysis techniques, namely after the data is collected, the next step is to describe the data completely, sequentially, and regularly, and after that the analysis is carried out by looking at each discussion of the themes discussed. Based on the results of this research, it is revealed that Nurcholish Madjid chose Islam that is more substantial than just symbolism. This is rooted in the universal values of Islam, not just the symbol of the